THE ANALYSIS OF ATTENUATION COEFFICIENT AND ACOUSTIC IMPEDANCE OF CEILING PANEL USING IMPEDANCE CHAMBER METHOD - Putramulyo, Satriogi; Wirawan, Rahadi; Alaa, Siti; Qomariyah, Nurul (Indonesian Physical Review, 2018)
The purposed of this research is to determine the attenuation coefficient and acoustic impedance of ceiling panel like plywood, calsiboard and bamboo woven. Â The influence thickness, paint coated, air cavity increment of the attenuation coefficient and acoustic impedance of these ceiling panel are also mesured. The impedance chamber method with range of frequency 100 Hz â€“ 5000 Hz are used here. The result shows that the average of attenuation coefficient for plywood panel, calsiboard panel and bamboo woven panel are 0,37 Npmm-1, 0,62 Npmm-1 and 0,28 Npmm-1 respectively. In addition, the acoustic impedance of these panel is 1,33 x 106 kgm-2s-1, 3,74 x 106 kgm-2s-1 and 1,15 x 106 kgm-2s-1. The attenuation coefficient is decreased with the increasing thickness of the panel and the same trend is founded of the acoustic impedance. Meanwhile, the paint coated can increase attenuation coefficient and acoustic impedance. For the air cavity increment ceiling panel, the attenuation coefficient and acoustic impedance are less than the solid panel.